(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
The practice of Hakam serves as a reconciliation process conducted in collaboration with appointed family panels and parties involved in divorce. Hakam also plays a role in obtaining the authority to pronounce talak (divorce) from the husband in the event of failed reconciliation. The issue is the abilities of the party’s representative to resolve disputes on behalf the disputant parties that deals with matrimonial cases. Therefore, the objective of this study focuses on the to identify Hakam from Islamic perspective, the implementation of Hakam in accordance with Shariah principles. The third objective is to examine the effective role of Hakam in resolving cases against disputing parties. The final objective of this study is to analyse the challenges of Hakam in Shariah Judicial System in Selangor and suggesting the resolutions. The methodology employed by the researcher is qualitative research method such as referring to books, journals, case study and interview session with the officer in charge for Hakam in Selangor. The study identifies existing gaps in the implementation of Hakam that can be clarified and refined. Based on these findings, the study proposes recommendations for refining and clarifying the implementation of Hakam in Shariah courts